WORKS DONE FOR THE DEVELOPMENT OF KINDERGARTEN IN UZBEKISTAN AND ITS EFFECTS - Arabboyeva , Mohichehra Ganijanovna (Educational Research in Universal Sciences, 2023)
In this article, the work carried out in the field of preschool education in our country, the statistics of kindergartens as of today, the positive and negative aspects of private kindergartens are covered in detail.